Just hire your spouse! Evidence from a political scandal in Bavaria - Björn Kauder; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
We investigate a case of political favoritism. Some members of the Bavarian parliamenthired relatives as office employees who were paid using taxpayers money. The familyscandal was a hot issue in the German media because of the upcoming state and federalelections. We examine whether being involved in the scandal influenced re-electionprospects and voter turnout. The results do not show that being involved in the scandalinfluenced the outcome and voter turnout of the 2013 state elections. Voters did notappear to punish the incumbent government because the reigning CSU endorses Bavarianidentity and managed to overcome the family scandal, as the CSU already managed toovercome previous scandals.
Keywords: D72; H70; A13; 330; Political scandal; favoritism; nepotism; re-election prospects; voter turnout